HAKIKAT GEREJA BERDASARKAN 1 PETRUS 2:9-10 DAN IMPLIKASINYA TERHADAP FENOMENA GEREJA DIGITAL DI ERA 4.0 - Aritonang, Boy Andi (Jurnal Matetes STT Ebenhaezer, 2022)
Abstract During the Covid-19 pandemic, there has been a digital church phenomenon that uses virtual worship in the process. So far, there weren’t any scholar that examine the biblical basis of the digital church phenomenon and its relationship to the 4.0 era. Existing research only discusses the phenomenon of digital churches only during the Covid-19 pandemic. So through this paper, the author wants to see the nature of the church according to the Bible and its implications for the digital church which is not only limited to the pandemic period, but also in the current 4.0 era. The method that will be used in this research is the exposition of the text of 1 Peter 2:9-10. The exposition found the essence of the church, that the church is